A Bird’s Eye View on Ojakshaya with Special Reference to Pandu(Anemia) - Solanki, Priyanka; krishnan, Ajith (International Research Journal of Ayurveda & Yoga, 2024)
It is considered that Ojas is a constituent that embodies the ultimate essence of each and every one of the body’s Dhatus, or tissue elements. It is one of the Pranayatanas, or the "seat of life." Ojas is also regarded as the live, luminous energy that resides within the human body. Every bodily component needs it to function efficiently. Both physiological and psychological elements have an impact on it. The classical Ayurveda text describes Ojakshaya as one of the Ojavikara which may be prevalent in various diseases. Referring to our ancient text, Pandu Roga is a disorder brought on by Oja kshaya in the body. Clinical evaluations of Pandu patients can reveal the presence of Oja kshaya; if this information is kept in mind during treatment, it may prevent the disease from progressing further and leading to problems. The relationship between Oja kshaya and Pandu is discussed in old Ayurvedic texts. The findings indicate that Oja kshaya may be more common in Pandu patients. The goal of this review article is to comprehend Oja and Oja kshaya and how they relate to Pandu..